The Effect of Intermittent Lighting Schedule on Broiler Performance - Rahimi, G.; Rezaei, M.; Hafezian, H.; Saiyahzadeh, H. (International Journal of Poultry Science, 2005)
In an experiment with complete randomized design, the effect of intermittent lighting (1 h L: 3 h D) was studied on performance of 400 broiler chicks from 10 to 42 d of age. During of the experiment feed intake, body weight, feed conversion ratio were measured weekly. Mortality was measured throughout the experiment. At 42 d of age 10 chicks from each treatment were slaughtered for abdominal fat weight. There wasn`t significant difference for body weight at 42 d between treatments. Use of intermittent lighting schedule improved feed conversion ratio significantly (P<0.05). Due to decrease fat deposition, intermittent lighting program reduced abdominal fat percentage (P<0.05). There wasn`t significant difference between treatments for mortality. In conclusion, since physical activity is very low during darkness, and energy expenditure for activity is reduced, therefore use of intermittent lighting program enhanced production efficiency, reduced room temperature and cost of electricity.